Management Reputation Analysis Related to the Holywings Case in Blasphemy - Nibras, Nabilah; Handoko, Gilang; Rizki Pangestu, Audi (Educationist: Journal of Educational and Cultural Studies, 2023)
Holywings is currently in the spotlight of discussion among the public because its employees were involved in a blasphemy case while promoting free liquor. In the news circulating on social media, Holywings uploaded a promotion via Instagram on June 23, 2022, in the form of free liquor for visitors named Muhmmad and Maria. then after being busy and tense, Holywings deleted the upload and then uploaded a post again, which is an apology on June 24, 2022.